Qualification of long-stored samples of serum banks for seroepidemiological studies - Böthig, B; Danes, L; Gerike, E; Ditmann, S; Svandová, E (Journal of hygiene, epidemiology, microbiology, and immunology, 1992)
Serum samples were tested for antibodies against polio virus and measles virus from two serum banks after having been stored under different conditions for several years. The results are compared with those ones obtained immediately after sampling. Despite of small increases of antibody-negative samples and of small decreases of the titres the suitability of the samples stored could be shown. Special attention should be given to the establishment, e.g. in the framework of Expanded Programme on Immunization of the World Health Organization and in order to study new pathogens unknown to date, and the technical preconditions for that should be planed.
Keywords: Kenya; kryoprezervace; Humans; Cryopreservation; spalničky; Nigérie; Keňa; séroepidemiologické studie; lidé; Togo; odběr vzorku krve; Germany; časové faktory; Německo; Blood Banks; krevní banky; Československo; Nigeria; Seroepidemiologic Studies; Poliomyelitis; Czechoslovakia; protilátky virové; Measles; Antibodies, Viral; Time Factors; poliomyelitida; Blood Specimen Collection